Reactions of 1-Amino-5-benzoyl-4-phenyl-1H-pyrimidine Derivatives with Various Isothiocyanates - ONAL, ZULBIYE; CANAN DAYLAN, A. (Asian Journal of Chemistry, 2010)
1-Amino-5-benzoyl-4-phenyl-1H-pyrimidine derivatives 1 react with the various isothiocyanates 2a-l under different conditions to yield the new N,N´-disubstituted thioureas 3a-l. The structures of these compounds 3a-l were determined by elemental analysis, IR, 1H and 13C NMR spectroscopic measurements.